Hemodynamic alterations with large spontaneous splenorenal shunt ligation during adult deceased donor liver transplantation - Chen, Guangshun; Li, Qiang; Zhang, Zhongqiang; Xie, Bin; Luo, Jing; Si, Zhongzhou; Li, Jiequn (Frontiers in Surgery, 2022)
Background A large spontaneous splenorenal shunt (SRS) will greatly impact portal inflow to the graft during liver transplantation (LT). Direct ligation of a large SRS is an uncommon surgical procedure and the hemodynamic consequences of this procedure are unknown. Methods In this retrospective study, we described our technique for direct ligation of a large SRS and the consequent hemodynamic changes during LT. 3-Dimensional computed tomography and Doppler ultrasonography were used to evaluate SRS and portal vein blood flow volume (PFV). Results A total of 22 recipients had large SRS including 13 with PFV <85 ml/min/100 g (ligation group) and 9 with PFV ≥85 ml/min/100 g (no ligation group). The diameter of SRS was significantly larger in the ligation group than in the non-ligation group (22.92 ± 4.18 vs. 16.24 ± 3.60 mm; p = 0.0009). In all ligation patients, the SRS was easily identified and isolated, it was located just below the distal pancreas and beside the inferior mesenteric vein. PV flow increased significantly from 68.74 ± 8.77 to 116.80 ± 16.50 ml/min/100 g (p < 0.0001) after ligation; this was followed by a reduction in peak systolic velocity of the hepatic artery from 58.17 ± 14.87 to 46.67 ± 13.28 cm/s (p = 0.0013). Conclusions Direct ligation of large SRS was an effective and safe surgical procedure to overcome the problem of portal hypoperfusion during LT.